AB1232 Estimating the economic value of a patient support program in rheumatoid arthritis in the united kingdom. (12th June 2018) - Ostor, A.; Garg, V.; Yang, M.; Chamberlain, C.; Skup, M.
Abstract : Background: A Patient Support Program (PSP) offered by AbbVie to adalimumab-treated patients assists them with issues pertaining to medication costs, nurse support, injection training, pen disposal, and medication reminders. A number of studies have reported the benefit of enrollment in this PSP from different perspectives, including clinical, patient-reported, and adherence outcomes. 1–2 There is limited information available on the economic value of the PSP. Objectives: To estimate the incremental economic value associated with enrollment in the PSP for adalimumab-treated patients with rheumatoid arthritis (RA) from a UK societal perspective. Methods: An Excel-based economic model was developed to describe adalimumab-treated PSP enrollees over non-enrollees in terms of a) improvement in clinical status as measured by the Health Assessment Questionnaire Disability Index (HAQ-DI], which resulted in reduced healthcare resource utilisation (HRU), and b) improvement in work productivity as measured by the Work Productivity and Activity Impairment Questionnaire (WPAI). The associated incremental direct and indirect cost savings were estimated over a 12 month period. Scores on HAQ-DI, work productivity impairment, and employment rate were obtained from a prospective, observational Phase IV study assessing patient satisfaction and outcomes in the context of the PSP (AbbVie Care) among RA patients (NCT01383421, PASSION) 1 . Inputs from literature and UK-specific publically available sources were used to model the association between HAQ-DI score categories (0 –<0.6, 0.6 –<1.1, 1.1 –<1.6, 1.6 –<2.1, 2.1–3) and HRU among RA patients, and to obtain unit costs of HRU (i.e., hospitalizations, specialist visits, imaging assessments) and weekly work compensation. Results: In PASSION, a greater proportion of PSP enrollees were in the lower HAQ-DI categories (i.e., better outcomes) and enrollees had greater reduction in total work impairment than non-enrollees after treatment with adalimumab. Assuming a population of 10 000 adalimumab-treated RA patients in the UK, this was associated with an incremental annual cost saving of £2, 320, 809 should all these patients enrol in the PSP. The largest proportion of incremental cost saving resulted from the reduction in RA-related hospitalizations (£1, 550, 637; 66.8%). Cost saving due to improved work productivity accounted for the second largest proportion (£686, 963, 29.6%). Specialist visits and imaging assessments accounted for 1.9% (£44, 564) and 1.7% (£38, 645) of the total incremental cost saving, respectively. Conclusions: Enrollment in AbbVie's PSP was shown to be associated with incremental cost saving among adalimumab-treated RA patients due to reduced resource utilisation and improved work productivity. References: [1] van Den Bosch F, et al. Rheumatol Ther. 2017;4:85–96. [2] Rubin DT, et al. J Manag Care Spec Pharm. 2017;23(8):859–867. Acknowledgements: Medical writing support was provided by Cheryl Q. Xiang of Analysis Group; this support was funded by AbbVie. Disclosure of Interest: A. Ostor Grant/research support from: Roche, Chugai, MSD, AbbVie, Pfizer, Novartis, Napp, Janssen, Lilly and BMS, Consultant for: Roche, Chugai, MSD, AbbVie, Pfizer, Novartis, Napp, Janssen, Lilly and BMS, V. Garg Shareholder of: AbbVie, Employee of: AbbVie, M. Yang Employee of: Analysis Group, Inc., which has received consultancy fees from AbbVie, C. Chamberlain Employee of: Analysis Group, Inc., which has received consultancy fees from AbbVie, M. Skup Shareholder of: AbbVie, Employee of: AbbVie